Respuesta :

Answer:

The value of f(1 + g(2)) is 5

Step-by-step explanation:

Let us solve the question

∵ f(x) = 2x - 3

∵ g(x) = x + 1

We need to find the value of f(1 + g(2))

That means we will replace x in f(x) by 1 + g(2)

→ g(2) means substitute x in g by 2

∵ g(x) = x + 1

∵ x = 2

∴ g(2) = 2 + 1

g(2) = 3

∵ x of f = 1 + g(2)

∵ g(2) = 3

∴ x of f = 1 + 3

x of f = 4

→ To find f(1 + g(2)) substitute 1 + g(2) by 4

∵ f(x) = 2x - 3

∵ x = 4

∴ f(4) = 2(4) - 3

∴ f(4) = 8 - 3

f(4) = 5

f(1 + g(2)) = 5

ACCESS MORE